2019
DOI: 10.3390/rs11101233
|View full text |Cite
|
Sign up to set email alerts
|

The Comparison of Different Methods of Texture Analysis for Their Efficacy for Land Use Classification in Satellite Imagery

Abstract: The paper presents a comparison of the efficacy of several texture analysis methods as tools for improving land use/cover classification in satellite imagery. The tested methods were: gray level co-occurrence matrix (GLCM) features, Laplace filters and granulometric analysis, based on mathematical morphology. The performed tests included an assessment of the classification accuracy performed based on spectro-textural datasets: spectral images with the addition of images generated using different texture analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
63
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(65 citation statements)
references
References 25 publications
2
63
0
Order By: Relevance
“…Furthermore, Culbert et al [38] documented that texture features can vary depending on the observed vegetation and its phenological stage, which makes it an interesting tool for multi-temporal studies. These facts are gaining more attention in research studies, mainly focusing on land cover classification [39][40][41], vegetation modelling [42,43] and structure [44,45] as well as forest biomass estimation [46,47]. For agricultural crops, there exist, to our best knowledge, only two studies using texture features in combination with UAV multispectral information.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Culbert et al [38] documented that texture features can vary depending on the observed vegetation and its phenological stage, which makes it an interesting tool for multi-temporal studies. These facts are gaining more attention in research studies, mainly focusing on land cover classification [39][40][41], vegetation modelling [42,43] and structure [44,45] as well as forest biomass estimation [46,47]. For agricultural crops, there exist, to our best knowledge, only two studies using texture features in combination with UAV multispectral information.…”
Section: Introductionmentioning
confidence: 99%
“…There are several indices derived from second-order statistical of GLCM reflecting texture characteristics. In our study, we adopted three texture indices called Contrast (CON), Entropy (ENT), and Correlation (COR), which have been proven to be effective in identifying heterogeneous objects [43][44][45]. These three texture indices are determined by following equations:…”
Section: Texture Information Extractionmentioning
confidence: 99%
“…The use of textural information in image classification, apart from spectral data, can significantly increase the accuracy of classification (Haralick et al 1973). The best results can be obtained by using a combination of spectral and textural data (Bekkari et al 2012;Kupidura 2019). Texture can be a distinctive feature of selected land cover classes exhibiting significant spectral similarities.…”
Section: Texture Analysismentioning
confidence: 99%
“…It has no unambiguous definition (Bracewell 2000), which is why in the practice of digital image processing many different methods of texture analysis have been defined. For this study, Fourier transform (Kupidura 2019) and computation of image statistics were applied for texture characterizations of study sites.…”
Section: Texture Analysismentioning
confidence: 99%